Modeling the U.S. firearms market: the effects of civilian stocks, crime, legislation, and armed conflicte - Brauer, Jürgen (2020)
This study represents an attempt to understand the U.S. firearms market – the largest in the world – in economic terms. A model of the underlying interplay of legal firearms supply and demand is a prerequisite for reliably evaluating the effectiveness of pertinent existing state and federal firearms policies, and to amend them as necessary. The stakes are high: compared to other nation-states, per capita firearms-related harm in the United States (including suicides and homicides) is exceptionally high and, within constitutional strictures, state and federal firearms policymakers increasingly view it as a major and pressing society-wide problem